A3_7 Babylon Gun Revisited - Cullis, Paul; Davenport, Liam; Durant, Emile (Physics Special Topics, 2012)
Abstract This paper investigates the Iraqi supergun that was under construction in 1988. The gun was never completed so its performance will be investigated using a model constructed from information about the gun. The maximum range of the gun fired at 33 degrees to the horizontal was investigated and found to be 1406km. Its impact angle was found to be 61 degrees and its impact velocity 2640m/s.Â 